2022
DOI: 10.3389/fsurg.2022.1035681
|View full text |Cite
|
Sign up to set email alerts
|

A novel scoring system to predict the residual back pain after percutaneous kyphoplasty for osteoporotic vertebral compression fracture

Abstract: ObjectiveTo establish a scoring system to predict the residual back pain after percutaneous kyphoplasty (PKP) for osteoporotic vertebral compression fracture (OVCF).Materials and methodsWe retrospectively reviewed the clinical records of 98 patients who were diagnosed of single-vertebral OVCF and underwent PKP surgery in our department from January 2015 to December 2017. The following clinical characteristics including age, gender, disease course, fracture location, fracture type, segmental kyphosis, and bone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 31 publications
0
4
1
Order By: Relevance
“…In our study, we also found that Type D cement form, where the cement does not contact the upper and lower endplates, is a risk factor for residual lower back pain after surgery. Additionally, Yang reported that cement injection volume less than 5ml 13 , and Yu reported that cement injection volume less than 3ml 26 are risk factors for postoperative residual lower back pain, but in our study, we did not nd a correlation between cement injection volume and postoperative residual lower back pain. Moreover, we also found correlations between residual back pain and progressive kyphosis, the Spearman's rank correlation coe cient is 0.618.…”
Section: Discussioncontrasting
confidence: 83%
See 3 more Smart Citations
“…In our study, we also found that Type D cement form, where the cement does not contact the upper and lower endplates, is a risk factor for residual lower back pain after surgery. Additionally, Yang reported that cement injection volume less than 5ml 13 , and Yu reported that cement injection volume less than 3ml 26 are risk factors for postoperative residual lower back pain, but in our study, we did not nd a correlation between cement injection volume and postoperative residual lower back pain. Moreover, we also found correlations between residual back pain and progressive kyphosis, the Spearman's rank correlation coe cient is 0.618.…”
Section: Discussioncontrasting
confidence: 83%
“…The NIBSS score is also one of the important risk factors for residual lower back pain after surgery. Yang et al reported that kyphotic angle greater than 20 degrees and AO type A4 fractures are high-risk factors for residual lower back pain after surgery 13 . In the NIBSS scoring system, the larger the preoperative and postoperative kyphotic angles, the higher the score.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the drawbacks of transpedicular PKP have also been reported, including residual back pain, facet joint violation, and cement leakage. Yang et al reported that 19 of 98 patients with single-level OVCF who underwent PKP experienced residual back pain (VAS score >4 at 6 months postoperatively) ( 15 ). Similarly, Li et al conducted a study to analyze the risk factors of residual back pain in OVCF patients after PKP.…”
Section: Discussionmentioning
confidence: 99%